Efectos de la aplicación de dentífricos con calcio, fosfato y fluoruro de sodio en piezas dentales que presentan desmineralización y caries inicial. Revisión bibliográfica - Cabrera Vaca, Daniel Francisco (2021)
The present study is a bibliographic type which aims to analyze the effectiveness of the application of remineralizing dentifrices based on calcium, phosphate and sodium fluoride in enamel of dental pieces which present demineralization or initial caries, for this, 37 articles from different bibliographic sources which met the inclusion and exclusion criteria were gathered. Currently, there are several remineralizing products in different presentations that promote remineralization and prevent the development of cavities. The implementation of Calcium Phosphate (APP ACP) to several of these products is a very efficient upgrading. Toothpastes and other remineralizing agents that have APP-ACFP show better results than other agents used for the same purpose. Several bibliographic sources (91.89%) mention that toothpastes containing calcium phosphate and fluoride have a great remineralizing effect on teeth with initial cavities. The 65.38% mention that the toothpastes containing APP-ACFP have a better remineralization effect compared to other remineralizing products and 80% mention that the degree of effectiveness of remineralization of toothpastes that have phosphate, calcium and fluoride in their composition is mostly significant. Key Words: Dentifrices, Tooth Remineralization, Dental Caries